«La mia avventura sono io». Individui e società dal linguaggio del movimento studentesco a quello delle riviste neofemministe - Chiara Martinelli (Laboratoire Italien)
Little attention has been paid to the analysis of individualism and libertarianism in student and feminist movements. This paper aims to highlight these subjects, by analysing differences and similarities between student protest and the women’s liberation movement with respect to their attitude towards society. To do this, we will study Noi donne (a pivotal magazine for the traditional Italian feminist movement) and the neo-feminist movement’s magazines Effe and Sottosopra, both of which were founded in 1973, but are characterised by a different ideological structure. This analysis reveals a shared vision of progress and how to achieve it: both movements assumed that progress could be achieved not by society and its oppressive structures, but by efforts made by individuals. Only if people learnt to free their true selves, overcoming prejudices and influences, could they liberate themselves from an oppressive and unfair society.